First online X‐ray fluorescence characterization of liquid‐liquid extraction in microfluidics. Issue 2 (29th June 2021) - Maurice, Ange A.; Theisen, Johannes; Rai, Varun; Olivier, Fabien; El Maangar, Asmae; Duhamet, Jean; Zemb, Thomas; Gabriel, Jean‐Christophe P.
Abstract: Liquid‐liquid extraction is a complex chemical purification process, which is associated with many thermodynamic and kinetic values. This makes its application in the recycling industry difficult, as it deals with waste streams that have highly variable compositions. In this regard, modelling an extraction process using microfluidics proves to be a useful approach to allow rapid adaptation to such composition changes, if development can be shown to be more accurate, faster, and safer than the classical batch approach with separate analysis. Here, the first automated microfluidic tool integrated with online X‐ray fluorescence (XRF) is reported to study liquid‐liquid extraction processes by enabling metal concentration quantification. The measurement is automated and performed for both aqueous and organic phases to improve accuracy. Overall, this fully automated approach shows that: (i) Thermodynamic and kinetic values associated with these processes can rapidly and efficiently be obtained simultaneously (in less than 13 hours with a resulting liquid use of less than 20 mL). (ii) Numerical simulations are consistent with the experimental data and provide rare insights regarding the respective contributions to the overall kinetic of the extraction system. Abstract : An X‐ray fluorescence is integrated for the first time with a liquid‐liquid extraction microfluidic platform and applied to the study of rare earth elements extraction. It allows the study of both thermodynamics and kinetics of the process in few hours, and prove the existence of an interface resistance anisotropy when comparing extraction to reverse extraction kinetics.